2023
DOI: 10.1007/s11214-023-01007-4
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Evolution of Enceladus’s Tidal Dissipation

Francis Nimmo,
Marc Neveu,
Carly Howett

Abstract: Enceladus possesses a subsurface ocean beneath a conductive ice shell. Based on shell thickness models, the estimated total conductive heat loss from Enceladus is 25–40 GW; the measured heat output from the South Polar Terrain (SPT) is 4–19 GW. The present-day SPT heat flux is of order $100\text{ mW}\,\text{m}^{-2}$ 100  mW m − 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…(2021) concluded that hydrogenotrophic methanogenesis still appears to be the metabolism with the highest energy yield and biomass potential. If Enceladus is younger than once thought (Ćuk & Moutamid, 2023; Ćuk et al., 2016; though see also Nimmo et al., 2023) and/or life is in the early stages of evolution, metabolic inefficiencies may explain some of the high Gibbs free energies inferred. Finally, spatial constraints (e.g., restricted space for a habitat on the seafloor) could limit access to H 2 despite it being readily available in solution, particularly if the ocean plume is rotationally controlled and spatially isolated to a column during transit to the ice layer (e.g., Choblet et al., 2017; Schoenfeld et al., 2023), though wider mixing of seawater with HF and longer timescales of vertical transport have been proposed (e.g., Kang et al., 2022).…”
Section: Discussionmentioning
confidence: 98%
“…(2021) concluded that hydrogenotrophic methanogenesis still appears to be the metabolism with the highest energy yield and biomass potential. If Enceladus is younger than once thought (Ćuk & Moutamid, 2023; Ćuk et al., 2016; though see also Nimmo et al., 2023) and/or life is in the early stages of evolution, metabolic inefficiencies may explain some of the high Gibbs free energies inferred. Finally, spatial constraints (e.g., restricted space for a habitat on the seafloor) could limit access to H 2 despite it being readily available in solution, particularly if the ocean plume is rotationally controlled and spatially isolated to a column during transit to the ice layer (e.g., Choblet et al., 2017; Schoenfeld et al., 2023), though wider mixing of seawater with HF and longer timescales of vertical transport have been proposed (e.g., Kang et al., 2022).…”
Section: Discussionmentioning
confidence: 98%
“…However, an overwhelming majority of measurable thermal emission from planetary bodies is due to blackbody radiation of absorbed sunlight and thus these measurements are better suited to calculating the body's albedo (e.g., Howett et al., 2010) rather than its background heat flux (cf. Howett et al., 2011a; Nimmo et al., 2023, for Enceladus, where the tiger stripes provide better measurement of internal heating). Radio‐tracked flybys could measure the spherical harmonic coefficients of gravity J 2 and C 2,2 , which we would expect to reveal a lower moment of inertia for a melted and differentiated ocean world compared to our inferred, ocean‐free Mimas.…”
Section: Discussionmentioning
confidence: 99%
“…These results require high dissipation in the present as well as in the past (see reviews by Nimmo et al. 2018 , 2023 ). Enhanced tidal dissipation within a porous (also called “fluffy”) core may be critical to explaining such high heat flows (Roberts 2015 ; Choblet et al.…”
Section: The Geology Of the Mid-sized Moonsmentioning
confidence: 99%
“…Whether Enceladus is currently in a state of equilibrium tidal heating or oscillating around an equilibrium depends on how dissipation is partitioned between Enceladus and Dione, as well as the evolution of Saturn’s Q, as discussed in detail by Nimmo et al. ( 2023 ). In addition, Enceladus may have experienced past epochs of higher eccentricity during the complex dynamical evolution of all five mid-sized moons (e.g., Meyer and Wisdom 2008 ; Běhounková et al.…”
Section: The Geology Of the Mid-sized Moonsmentioning
confidence: 99%